Analysis of MSME Taxpayer Compliance with Tax Regulations in Indonesia - Aidah, Mus; Saiful, Saiful; Andika, Mohammad; Risaldi, Moh.; Romadhona, Agus (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the compliance of MSME taxpayers with tax regulations in Indonesia. This study employs a qualitative approach, utilizing a case study research design. The research was conducted in areas with a high concentration of MSMEs, which were selected purposively. Informants consisted of MSMEs who have registered as taxpayers, tax officers from the Tax Service Office (KPP), and tax consultants who handle MSMEs. Data collection techniques included in-depth interviews, observation, and documentation studies. Meanwhile, data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions and verification. The results of this study indicate that the level of MSME taxpayer compliance with tax regulations in Indonesia is influenced by their understanding, perception, and experience in carrying out tax obligations. Low tax literacy, administrative complexity, and a lack of trust in the government are the primary obstacles to achieving optimal compliance. However, an educational and personalized approach from the tax authorities is considered effective in building awareness and encouraging MSMEs to comply with tax obligations voluntarily.